The Implementation of Project-Based Learning in English Learning Classroom in SMK Terpadu Lampang - Sapari, Gigin Ginanjar; Meinita, Meinita; Nurmala, Ela (Journal of English Education, Literature and Linguistics, 2024)
Project-based learning is a teaching approach designed for students, enabling them to solve problems through a series of learning activities and real-world tasks. The aims of this research are to find out the process of the implementation of project-based learning methods in English learning classrooms and the impact of using project-based learning methods in English learning classrooms on student critical thinking. This study uses a qualitative method with a descriptive design. The data sources for this study came from observations and interviews. Based on the results of the study, it shows that the English learning process in the classroom using project-based learning has the same aspects as the theory. It can be seen that teachers do preparation, planning, research, conclusion, showing the findings, and evaluation. And using project-based learning also has an impact on students' critical thinking. It can be seen from some aspects that students have reached levels C4, C5, and C6, or High Order Thinking Skills (HOTS), which indicate that they can give examples of what they learn and how they answer questions given by the researcher.